Development of an Augmented Reality–Based Geometry Module to Enhance Students’ Understanding of Three-Dimensional Concepts - Parandreni, Mursyidah J. (Aksioma Education Journal, 2024)
This study aims to develop and evaluate an Augmented Reality (AR) based geometry module intended to improve students’ understanding of three dimensional (3D) concepts. The research responds to the persistent challenges students face in visualizing geometric solids and interpreting spatial relationships, which commonly result in misconceptions in geometry learning. A research and development (R&D) approach was applied to 126 junior high school students selected through cluster sampling. Data were gathered using pre-tests, post-tests, spatial ability assessments, and motivation questionnaires, supported by classroom observations. The results revealed a significant increase in students’ conceptual understanding and spatial reasoning after using the AR-based module. Students also demonstrated higher motivation and engagement throughout the learning process. Data analysis indicated strong effect sizes and substantial normalized gains, confirming the effectiveness of AR in enhancing 3D geometry comprehension. The AR module succeeded in transforming abstract geometric content into interactive and concrete representations, thereby supporting meaningful learning. This study concludes that AR is a promising tool for improving both cognitive and affective learning outcomes in mathematics.